Bilateral lateral rectus muscle recession versus unilateral lateral rectus recession with medial rectus resection: a 12-month outcome analysis for intermittent exotropia - Qi, Li; Bian, Xiaoyan; Wang, Wei; Jia, Jianxin (Frontiers in Ophthalmology, 2025)
BackgroundIntermittent exotropia (IXT) is a common form of strabismus, often treated surgically to improve ocular alignment and binocular vision. This study compares the outcomes of two surgical techniques: bilateral lateral rectus recession (BLRR) and unilateral lateral rectus recession combined with medial rectus muscle resection (ULRRMMR), focusing on sensory eye alignment, stereopsis function, and binocular vision recovery.MethodsThis retrospective study included 306 children with intermittent exotropia, assigned to either the BLRR or ULRRMMR group. Participants were evaluated preoperatively and at 1-, 3-, and 12-months post-surgery for sensory alignment, stereopsis, binocular vision, and complications. Statistical analyses were conducted to compare the outcomes between the two groups.ResultsAfter surgery at one day, overcorrection was observed more frequently in the BLRR group (P = 0.02). A comparison of the two surgical approaches revealed that the BLRR group demonstrated significantly greater improvements in sensory eye alignment (P = 0.009). In contrast, the ULRRMMR group showed superior outcomes in terms of foveal stereopsis (P = 0.01), binocular vision recovery (P = 0.007), and achieving normal eye alignment (P < 0.001) at 12 months. Notably, there was no significant difference in the rate of complications or binocular vision recovery between the two groups at the 12-month follow-up (P = 0.822).ConclusionBoth BLRR and ULRRMMR are effective treatments for intermittent exotropia, but the BLRR may be a more optimal choice for enhancing sensory alignment, while ULRRMMR technique offers superior recovery in terms of stereopsis, and binocular vision recovery.